Deconstructing emotion regulation in schizophrenia: The nature and consequences of abnormalities in monitoring dynamics - Bartolomeo, Lisa A.; Raugh, Ian M.; Strauss, Gregory P. (Schizophrenia research, 2022)
Prior studies implicate abnormalities at the identification, selection, and implementation stages of Gross’ extended process model of emotion regulation in schizophrenia. However, it is unclear whether monitoring dynamics (i.e., emotion regulation maintenance, switching, and stopping), another critical component of the model, are also abnormal or what predicts those abnormalities. The current study evaluated switching (i.e., switching to a different emotion regulation strategy because the initial strategy was not effective) and stopping dynamics (i.e., terminating the implementation of an emotion regulation strategy) and their associated mechanisms using 6 days of ecological momentary assessment in 47 outpatients with schizophrenia or schizoaffective disorder (SZ) and 52 healthy controls (CN). Results indicated that individuals with SZ exhibited excessive switching between emotion regulation strategies and delayed stopping compared to CN, self-efficacy moderated group differences in stopping abnormalities, and switching and stopping abnormalities were associated with different patterns of state-level positive and negative symptoms in SZ. Findings may inform psychosocial emotion regulation therapies for SZ that could incorporate elements for monitoring dynamics and associated mechanisms.